Comparative study of telecommunications policies in Hong Kong, Malaysia and Singapore. - Chong, Patrick Piang Teng. (2011)
To a large extent, the rise of new telecommunications operators in recent years in the Asia- Pacific has been triggered by important policy reforms. Most countries in the region have embraced some form of liberalization and have developed a number of legal instruments to foster private investment in the telecommunications sector. In the emerging economies—which account for the largest number of countries and population of the region—market reform has taken a different path than those of the more developed countries. In most of these nations, privatization of the national carrier has been largely absent or has been confined to a limited number of shares sold in the stock market mostly to local investors. Competition has been introduced in selected segments of the market, while the state has kept—in the form of ownership and'or regulation—a strong presence in the sector.